Goody, Polanyi and Eurasia: An Unfinished Project in Comparative Historical Economic Anthropology - Hann, Chris (History & Anthropology, 2015)
Goody's essay overlaps with his recent work on the “search for metals” and, more generally, with his many books expounding the commonalities of Eurasian history. His critique of Eurocentrism remains invaluable. This review article argues that his emphasis on diffusion can be usefully supplemented with a concept of civilization, to facilitate comparative structural analysis. Goody's perspective might also be enhanced by an engagement with the literature on “Axial Age” cosmologies and with substantivist economic anthropology. It is worth revisiting Karl Polanyi's efforts to grasp the position of the economy in society, in order to recover in the neoliberal present the long-run Eurasian dialectic between redistribution and market exchange.
Anthropology
Keywords: Eurasia; GOODY; Jack; 1919-2015; civilization; culture diffusion; economic anthropology

Migration, Precarization and the Democratic Deficit in Global Governance - Schierup, Carl-Ulrik; Ålund, Aleksandra; Likić-Brborić, Branka (International Migration, 2015)
This article attempts to provide a critical understanding of the dual signification of “precarity”. It explores what “precarity” as a concept may potentially offer to studies of the changing contemporary political economy of migration. It discusses shifting trends in global migration and point to tendencies for a possible convergence between “South” and “North”, “East” and “West”. Based on a review of current advances in research, it discusses, with reference to the classical work of Karl Polanyi, the potential for a contemporary “countermovement” which would challenge the precarity of migrants. Bringing forward the issue of the “space for civil society” the article addresses a still lingering democratic deficit in the global governance of migration. Policy Implications The article is relevant to policymakers, trade unions and civil society organizations. It contributes to the understanding of policy making processes in emerging multilevel global governance and focuses on issues of precarization, migration, and the implementation and accountability of human, migrant and labour rights.
Sociology; Anthropology
Keywords: countermovement; democratic deficit; ethnicity; global governance; migration; precarity; social welfare studies

After ideocracy and civil society Gellner, Polanyi and the new peripheralization of Central Europe - Hann, Chris (Thesis Eleven, 2015)
Behind only that of Bronislaw Malinowski, the influence of the Central European polymaths Ernest Gellner and Karl Polanyi on socio-cultural anthropology in the 20th century was profound. Gellner and Polanyi also influenced much wider swathes of scholarship. They belong to different generations and were raised in quite different settings in Prague and Budapest respectively. What these thinkers have in common is a philosophy of history which posits the industrial revolution in northwest Europe as a radical rupture in Weltgeschichte. Polanyi’s ‘great transformation’, with its focus on the economy, corresponds to Gellner’s metaphor of the ‘big ditch’ and focus on a new polity. The cultural homogenization of the nation-state and the disembedding of the economy from society in the era of free trade are two sides of the same coin. This paper argues that these complementary models derive to a considerable degree from the scholars’ background on the margins of industrializing Europe, in the ruins of the Habsburg Empire.
Anthropology
Keywords: Central Europe; GELLNER; Ernest; anthropology; civil society